Panduan Self Instruction dengan Pendekatan Structured Learning Approach untuk Menurunkan Prokrastinasi Akademik Siswa SMP - Erma Pratiwi Nufi; Arbin Janu Setiyowati; Diniy H. Rahman (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this research is to produce a training guide product that meets the acceptance criteria. This study uses Borg & Gall model research design. The data obtained in the form of quantitative data include aspects of accuracy, utility, propriety, and feasibility. The research subjects are BK experts, media experts, and potential users. The research instrument included BK experts instruments, media experts instrumen and scale of procrastination. Data analysis techniques used an interater agreement. The results show that the results from BK have a validity index 0,73